2011
DOI: 10.1016/j.aprim.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

La salud de los médicos de familia: ¿practicamos lo que predicamos?

Abstract: Adherence to cardiovascular and female cancer screening is adequate, but insufficient in colorectal cancer. Vaccination among the participants was adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…In a study conducted among hospital-based physicians in Israel, less than half of physicians actually underwent the tests themselves, although 94% of them reported that they believe in the importance of screening tests for physicians [ 15 ]. Similar findings were reported in other countries regarding non-adherence to regular screening for colorectal, cervical and breast cancer [ 31 , 32 , 33 ]. One of the barriers mentioned by physicians was lack of time.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted among hospital-based physicians in Israel, less than half of physicians actually underwent the tests themselves, although 94% of them reported that they believe in the importance of screening tests for physicians [ 15 ]. Similar findings were reported in other countries regarding non-adherence to regular screening for colorectal, cervical and breast cancer [ 31 , 32 , 33 ]. One of the barriers mentioned by physicians was lack of time.…”
Section: Discussionsupporting
confidence: 90%
“…When it comes to cancer screening, the compliance for different types varied. The adherence to colon cancer screening was low in this survey (37.8%); this is slightly better than that reported among PCPs in Spain (24%), 11 but much worse than that reported among Israeli PCPs (60.9%) 6 and US physicians (75%). 3 As for breast cancer, more than two-thirds of the female physicians in Lebanon screen for it through mammograms, a result that correlates with the literature.…”
Section: Discussioncontrasting
confidence: 76%
“…9,10 As for vaccination, Lebanese PCPs’ adherence to influenza and tetanus vaccines was similar to the rates reported in the literature. 6,9,11 However, adherence rate to pneumococcal vaccine was far less than that reported among Israeli PCPs in 2013 (44.5%). 6…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation